A repeated-measures examination of organizational stressors, perceived psychological and physical health, and perceived performance in semi-elite athletes - Simms, M.; Arnold, R.; Turner, J. E.; Hays, K. (Journal of Sports Sciences, 2020)
Organizational stressors can undermine the psychological well-being and performance of athletes. Less is known, however, about how these relationships unfold over time and whether organizational stressors can impact upon perceived physical health. The current study, therefore, used a repeated-measures design to examine relationships between organizational stressors with components of perceived psychological (anxiety and depression) and physical (illness symptoms and missed training days via illness) ill-health, and perceived performance at the within-person level. Twenty-three semi-elite female rowers completed monthly measures of study variables for six-months. Multilevel models indicated that selection-related stressors positively predicted symptoms of perceived psychological and physical ill-health, and negatively predicted perceived performance. Conversely, coaching stressors negatively predicted symptoms of perceived psychological ill-health. Logistics and operations stressors positively predicted perceived performance, whereas goals and development stressors negatively predicted perceived performance. These findings demonstrate for the first time that, with a repeated-measures design, organizational stressors can predict components of perceived physical and psychological ill-health, and perceived performance at the within-person level in athletes. From a practical perspective, practitioners should incorporate these findings when diagnosing the need for, developing, and optimally implementing primary and secondary stress management interventions.